ANALYSIS OF EXPERIENTAL FUNCTION IN INTERNET ADVERTISEMENTS - Rafika Purba (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2013)
AbstractThe research deals to experiental function. the problems of the study are What type of processes is dominantly used interned advertisement and Why are the dominant realities used. The objectives of the study are to investigate the dominant type of process used in advertisement and to describe causes of using the dominant types of processes in internet advertisements. the writer will collect the data qualitative research (qualitative data), and data will be get from some advertisements in Internet. From the data, the writer has found from the result of the research. it will be fact with the theory that advertising is an instance discourse.Keywords : English, Experiental Function, Internet Advertisements